2015
DOI: 10.31186/jagrisep.14.1.108-119
|View full text |Cite
|
Sign up to set email alerts
|

Faktor Yang Berhubungan Dengan Motivasi Menyimpan Hasil Panen Padi Petani Di Kabupaten Seluma

Abstract: The purposes of this research are to 1) estimate the frequency of sale until the next harvest season, 2) examine the reasons for saving the crops of rice farmers do, 3) reveal motivation of rice farmers to store their products, and 4) analyze the factors related to the motivation of storing crops of rice farmers in the County of Seluma. The results showed that the frequency of the sale of the crops that farmers is low. Economic reasons farmers saving the crops with the largest percentage of 36,67% was to be so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
0
1
3
Order By: Relevance
“…Respondent farmers whose yields are quite a lot will be more interested in transacting with the Warehouse Receipt System. In contrast to the results of the research [8] which showed the results that the amount of production in the previous planting season was not significantly related to the motivation to store crops. Farmer respondents do storage not because of a lot or least amount of production of crops in the last season, but based on willingness and need.…”
Section: Relationship Between Characteristics Of Farmers Andcontrasting
confidence: 95%
See 1 more Smart Citation
“…Respondent farmers whose yields are quite a lot will be more interested in transacting with the Warehouse Receipt System. In contrast to the results of the research [8] which showed the results that the amount of production in the previous planting season was not significantly related to the motivation to store crops. Farmer respondents do storage not because of a lot or least amount of production of crops in the last season, but based on willingness and need.…”
Section: Relationship Between Characteristics Of Farmers Andcontrasting
confidence: 95%
“…Therefore, farmers tend to be interested in implementing the Warehouse Receipt System. The results of this study are in line with the results of [8] which states that farming experience is significantly related to their motivation for storing crop yields because the length of experience of the farmer in the effort to guarantee an increase in the willingness to save the harvest.…”
Section: Relationship Between Characteristics Of Farmers Andsupporting
confidence: 88%
“…Perkembangan usaha agribisnis semangka di Indonesia berfluktuatif. Adanya fluktuasi tersebut kemungkinan disebabkan motivasi dalam berbudidaya semangka yang masih rendah dan lemahnya lembaga pertanian dalam memberikan dukungan informasi dan teknologi kepada petani (Departemen Pertanian, 2011 Faktor-faktor yang memotivasi petani yang merupakan faktor internal atau datang dari dalam diri petani antara lain umur, pendidikan, luas lahan, dan jumlah tanggungan (Kusuma, 2014). Tujuan dari penelitian ini adalah untuk mengetahui faktor-faktor apa saja yang memotivasi petani dalam melakukan usahatani semangka di Desa Sumber Sari, Kecamatan Kota Bangun.…”
Section: Pendahuluanunclassified
“…diperoleh signifikansi sebesar 0,001, hal ini menjelaskan bahwa signifikansi sebesar α 0,01 yang berarti terima H1, yaitu adanya korelasi sangat nyata pada taraf kepercayaan (99%). Hal ini sejalan dengan penelitian yang dilakukan Kusuma, Sriyoto, dan Priyono (2015) yang menyatakan ada hubungan yang nyata antara pendidikan dengan motivasi petani dalam kegiatan usahatani dalam penggunaan benih hibrida.…”
Section: Hubungan Antara Pendidikan Dengan Motivasi Pemuda Taniunclassified